Factorization of Perfect Square Trinomials | How to Factor Perfect Square Trinomials?

If you are searching for help on Factorization of Perfect Square Trinomials you are the correct place. Check out all the problems explained in this article. We have given a detailed explanation for every individual problem along with correct answers. Also, we are providing all factorization concepts, worksheets on our website for free of cost. Therefore, learn every concept and improve your knowledge easily.

Learn to solve the given algebraic expressions using the below formulas.
(i) a2 + 2ab + b2 = (a + b)2 = (a + b) (a + b)
(ii) a2 – 2ab + b2 = (a – b)2 = (a – b) (a – b)

Factoring Perfect Square Trinomials Examples

1. Factorization when the given expression is a perfect square

(i) m4 – 10m2n2 + 25n4

Solution:
Given expression is m4 – 10m2n2 + 25n4
The given expression m4 – 10m2n2 + 25n4 is in the form a2 – 2ab + b2.
So find the factors of given expression using a2 – 2ab + b2 = (a – b)2 = (a – b) (a – b) where a = m2, b = 5n2
Apply the formula and substitute the a and b values.
m4 – 10m2n2 + 25n4
(m2)2 – 2 (m2) (5n2) + (5n2)2
(m2 – 5n2)2
(m2 – 5n2) (m2 – 5n2)

Factors of the m4 – 10m2n2 + 25n4 are (m2 – 5n2) (m2 – 5n2)

(ii) b2+ 6b + 9

Solution:
Given expression is b2+ 6b + 9
The given expression b2+ 6b + 9 is in the form a2 + 2ab + b2.
So find the factors of given expression using a2 + 2ab + b2 = (a + b)2 = (a + b) (a + b) where a = b, b = 3
Apply the formula and substitute the a and b values.
b2+ 6b + 9
(b)2 + 2 (b) (3) + (3)2
(b + 3)2
(b + 3) (b + 3)

Factors of the b2+ 6b + 9 are (b + 3) (b + 3)

(iii) p4 – 2p2 q2 + q4

Solution:
Given expression is p4 – 2p2 q2 + q4
The given expression p4 – 2p2 q2 + q4 is in the form a2 – 2ab + b2.
So find the factors of given expression using a2 – 2ab + b2 = (a – b)2 = (a – b) (a – b) where a = p2, b = q2
Apply the formula and substitute the a and b values.
p4 – 2p2 q2 + q4
(p2)2 – 2 (p2) (q2) + (q2)2
(p2 – q2)2
(p2 – q2) (p2 – q2)
From the formula (a2 – b2) = (a + b) (a – b), rewrite the above equation.
(p + q) (p – q) (p + q) (p – q)

Factors of the p4 – 2p2 q2 + q4 are (p + q) (p – q) (p + q) (p – q)

2. Factor using the identity

(i) 25 – a2 – 2ab – b2

Solution:
Given expression is 25 – a2 – 2ab – b2
Rearrange the given expression as 25 – (a2 + 2ab + b2)
a2 + 2ab + b2 = (a + b)2 = (a + b) (a + b)
25 – (a + b)2
(5)2– (a + b)2
From the formula (a2 – b2) = (a + b) (a – b), rewrite the above equation.
[(5 + a + b)(5 – a – b)]

(ii) 1- 2mn – (m2 + n2)

Solution:
Given expression is 1- 2mn – (m2 + n2)
1- 2mn – m2 – n2
1 – (2mn + m2 + n2)
1 – (m + n)2
(1)2 – (m + n)2
From the formula (a2 – b2) = (a + b) (a – b), rewrite the above equation.
(1 + m + n) (1 – m + n)

Leave a Comment

Scroll to Top